PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEMBAKARAN RUMAH DI PELABUHAN KABUPATEN PENAJAM PASER UTARA - Jurniati Jurniati; Rini Apriyani; Orin Gusta Andini (INTELIGENSIA MEDIA, 2024)
The crime of burning a house requires law enforcement and legal accountability because it is a criminal act that violates Article 187 of the Criminal Code relating to the crime of burning a house and is the authority of law enforcement officials to enforce the law against perpetrators of house burning and is subject to punishment in accordance with the article imposed. The research approach was carried out using social and legal by conducting interviews with law enforcement officials, namely the East Kalimantan Regional Police, as well as interviews with Paser traditional heads regarding Paser traditional rituals related to house burnings that occurred in North Penajam Paser Regency, which aims to analyze two main points. The discussion is related to the law enforcement process against the perpetrators of house arson in North Penajam Paser Regency and the obstacles to law enforcement. The results of the research show that in the law enforcement process carried out by the East Kalimantan Regional Police, they were only temporarily detained and released because they were afraid it would cause bigger problems and endanger many people, therefore the East Kalimantan Regional Police carried out mediation with both parties between the Bugis and Paser traditional tribe with traditional peace rituals because it is a social conflict.